2022
DOI: 10.29244/agrokreatif.8.3.329-338
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Pendampingan Inovasi Produk Olahan Kopi di Desa Palak Tanah, Muara Enim

Abstract: Coffee is one of the leading commodities in Muara Enim Regency, South Sumatra Province. The coffee commodity is the backbone of the village community's economy, especially in the highlands of South Sumatra. One of them is Palak Tanah Village, Muara Enim Regency. The coffee commodity has been processed by farmers from generation to generation with an economic chain that still relies on tokeh (local collectors). Selling coffee beans that are still raw and unprocessed has no added value to the community's economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Martin et al also reported that the Semendo peasant has a subsistence ethic, so they do not immediately accept innovation [12]. Semendo coffee commodities are also processed traditionally, with a marketing chain that still depends on local traders whose commodities are raw coffee beans [13]. Existing marketing channels make coffee farmers the parties most vulnerable to market failure.…”
Section: Introductionmentioning
confidence: 99%
“…Martin et al also reported that the Semendo peasant has a subsistence ethic, so they do not immediately accept innovation [12]. Semendo coffee commodities are also processed traditionally, with a marketing chain that still depends on local traders whose commodities are raw coffee beans [13]. Existing marketing channels make coffee farmers the parties most vulnerable to market failure.…”
Section: Introductionmentioning
confidence: 99%